2022
DOI: 10.3389/fimmu.2022.954339
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of gut microbes and host’s immune response in gut–lung homeostasis

Abstract: The vast diversity of microbial communities reside in various locations of the human body, and they are collectively named as the ‘Human Microbiota.’ The majority of those microbes are found in the gastrointestinal and respiratory tracts. The microorganisms present in the gastrointestinal and the respiratory tracts are called the gut microbiota and the airway microbiota, respectively. These microbial communities are known to affect both the metabolic functions and the immune responses of the host. Among multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 82 publications
0
32
0
Order By: Relevance
“…Alterations in microbiota can be also present in asthma patients [ 60 , 61 ]. Recent studies showed that gut and lung microbiota are closely interconnected (“gut–lung axis”) and can be involved in the pathogenesis of asthma [ 62 ]. In particular, a significantly reduced presence of Lactobacillus can be of great importance [ 57 , 60 , 61 , 62 , 63 ].…”
Section: Clinical Overlap Between Asthma and Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in microbiota can be also present in asthma patients [ 60 , 61 ]. Recent studies showed that gut and lung microbiota are closely interconnected (“gut–lung axis”) and can be involved in the pathogenesis of asthma [ 62 ]. In particular, a significantly reduced presence of Lactobacillus can be of great importance [ 57 , 60 , 61 , 62 , 63 ].…”
Section: Clinical Overlap Between Asthma and Pcosmentioning
confidence: 99%
“…Recent studies showed that gut and lung microbiota are closely interconnected (“gut–lung axis”) and can be involved in the pathogenesis of asthma [ 62 ]. In particular, a significantly reduced presence of Lactobacillus can be of great importance [ 57 , 60 , 61 , 62 , 63 ]. If gut microbiota is altered, endotoxins are generated that may contribute to chronic inflammation in asthma patients by activation of NF-κB pathway [ 64 , 65 ].…”
Section: Clinical Overlap Between Asthma and Pcosmentioning
confidence: 99%
“…Normal flora benefits human health through mucosal homeostasis maintenance, promoting immune status, and being reactive in drug metabolism and metabolite utilization [1,2]. Multiple probiotic strains have been isolated and identified from human flora [3].…”
Section: Introductionmentioning
confidence: 99%
“…Various genetic and environmental factors contribute to the increasing incidence of UC. [1][2][3] Extraintestinal manifestations (EIM) may occur in up to 24% of patients with IBD before the onset of intestinal symptoms. EIM most commonly occur in joints, skin, eyes, and other parts, but numerous studies have shown that lung injury caused by IBD should not be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…9 On the other hand, intestinal microbiota and microbial metabolites are also involved in maintaining immune homeostasis in distal mucosal sites, especially in the lungs. 3,10 We have previously found that intestinal microbial diversity and composition in mice with colitis and concurrent lung inflammation are dramatically different from those in their controls. 9 Short-chain fatty acids (SCFAs), as important microbial metabolites from the microbial fermentation of dietary fiber, are also a major bridge for metabolic and immune signaling within the gut-lung axis.…”
Section: Introductionmentioning
confidence: 99%